Documentation of Unusual, Fall Spawning by Coastal Cutthroat Trout in the Elwha River System, Washington. Issue 6 (30th October 2014) - McMillan, John R.; R. Pess, George; McHenry, Michael L.; Moses, Raymond; Quinn, Thomas P.
Abstract: The timing of breeding is a key trait, reflecting selective forces acting on the adults and offspring in the population, contributing to reproductive isolation, and affecting the population's success during rapid environmental change. Salmon and trout populations vary greatly in the peak and range of breeding dates, and timing is a defining trait for salmonid populations. This study reports the occurrence and details of spawning by Coastal Cutthroat Trout Oncorhynchus clarkii clarkii in Indian Creek in the Elwha River, Washington, in October and November. This is unusually early in the season for this characteristically spring‐spawning species and is much earlier than conspecifics elsewhere in the river system and the region. We hypothesize that the stream's low gradient and lake‐dampened hydrologic regime reduced the depth of gravel scouring in the fall, and thus permitted the evolution of such an early breeding date by these small‐bodied (ca. 20–35 cm) fish. The exclusion of otherwise sympatric, fall‐spawning Coho Salmon O. kisutch for the past century from the habitat by Elwha Dam may also have contributed to this adaptation, and the recolonization by the larger and later‐spawning Coho Salmon may have affected the Coastal Cutthroat Trout through redd disturbance. Received April 24, 2014; accepted August 27, 2014